Lymphoma in Pregnancy: Case Report, Multidisciplinary Management and Anesthetic Approach - Pinto, Mariana (2021)
Lymphoma is the fourth most frequent cancer diagnosed during pregnancy, complicating about one in 6.000 pregnancies. The clinical approach must be based on a multidisciplinary medical team, involving collaboration from various medical specialties, in order to optimize maternal and fetal well-being. The anesthesiologist should gather of the patient’s clinical information, from the different medical specialties, in order to arrange the best anesthetic approach. We describe a case of a 35-year-old pregnant woman diagnosed with a lymphoma of anterior mediastinum complicated with large volume pericardial effusion, superior vena cava syndrome and bronchial compression by the mediastinal mass and pulmonary congestion with hypoxemic respiratory insufficiency. She was proposed to elective cesarian section. The multidisciplinary management of this clinical situation was crucial. The anesthetic approach to this case was based on the best anesthetic technique considering the pregnant women’s clinical condition, chemotherapy’s possible side effects and the well-being of the fetus.